Thyroid Cancer A Comprehensive Guide to Clinical Management - Wartofsky, Leonard; Van Nostrand, Douglas (Humana Press : Imprint: Humana, 2006)
In a massive updating of the highly acclaimed Thyroid Cancer: A Comprehensive Guide to Clinical Management, Drs. Leonard Wartofsky, Douglas Van Nostrand, and an expert group of contributing authors present a wealth of new information and insights on every aspect of the etiology, pathogenesis, diagnosis, initial treatment, and long-term management of all varieties of thyroid cancer. Paramount to this new edition is a thorough treatment of the nuclear medical aspects of diagnosing and managing the thyroid cancer patient. This includes extensive discussion of isotopes, isotope uptake and scanning procedures, radioiodine ablation and dosimetry (with or without recombinant human TSH), stunning, octreotide and FDG-PET scanning, and various alternative imaging modalities. Additional highlights include management of the scan-negative and thyroglobulin-positive patient, ultrasound of the lymph nodes, local adjuncts to therapy of metastases, low iodine diets and cookbooks, future directions in therapy, and alternative therapies when traditional surgery and radioactive iodine fail. Encyclopedic and definitive, Thyroid Cancer: A Comprehensive Guide to Clinical Management, Second Edition, offers clinical endocrinologists, nuclear medicine physicians, pathologists, oncologists, endocrine surgeons, and internists an authoritative guide to the optimal diagnosis and treatment of thyroid cancer today.